Hyperarousal during sleep in untreated, major depressed subjects with prodromal insomnia: A polysomnographic study. (December 2017) - Hein, Matthieu; Senterre, Christelle; Lanquart, Jean-Pol; Montana, Xavier; Loas, Gwénolé; Linkowski, Paul; Hubain, Philippe
Abstract: In primary insomnia, specific dynamics of hyperarousal are evident during the night. Similarly, in major depression, many elements also favor of the presence of hyperarousal. Thus, it would be interesting to investigate if hyperarousal presents the same dynamic in major depression. Polysomnographic data from 30 healthy controls, 66 patients with major depression and prodromal insomnia, and 86 primary insomnia sufferers recruited from the sleep laboratory database were studied for whole night and thirds of the night. Insomnia sufferers and patients with depression exhibit a similar polysomnographic pattern both for whole night (increased sleep latency and WASO and reduced SWS and REM) and thirds of night (increased WASO at first and last thirds, reduced SWS in first third, and reduced in REM in first and last third). No alterations were detected during the second third of the night. Just as in primary insomnia, the hyperarousal phenomenon is found mainly in major depression with prodromal insomnia during the sleep-onset period and the first and last thirds of the night, but lesser during the second third of the night. These specific dynamics of hyperarousal may aid in the understanding of the particular relationship between insomnia and depression. Highlights: Hyperarousal occurs in major depression with prodromal insomnia. Hyperarousal occurs during sleep onset and the first and last thirds of the night. Hyperarousal may leads to a deficiency of SWS and REM. New therapies should be considered for major depression with insomnia.